The quilter's homecoming eaudiobook - Chiaverini, Jennifer (Elm Creek Quilts, 2015)
Jennifer Chiaverini's popular Elm Creek Quilts series has been an international hit. The year is 1924. Elizabeth loves Elm Creek, but she's also dreamed of traveling the world. When her beloved Henry finally professes his love, he asks her to leave with him and move to a California ranch. Elizabeth must decide whether she can really leave her home behind forever. She may dream of travel, but she always envisioned herself ending up at Elm Creek.